Biology of BCG response in non-muscle invasive bladder cancer - 2021 IBCN Updates Part III - Reike, M. J.; Ingersoll, M. A.; Müller, D. C.; Zuiverloon, T. C.M.; Strandgaard, T.; Kamat, A. M.; Williams, S. B.; Seiler, R.; Todenhöfer, T.; Dyrskjøt, L.; Nawroth, R.; Goebell, Peter; et al. (Urologic Oncology-Seminars and Original Investigations, 2022)
Bacillus Calmette-Guerin (BCG) remains the only FDA-approved first-line therapy in patients with high-risk non-muscle invasive bladder cancer. Recurrences, even after adequate BCG therapy, are common and the efficacy of second-line therapies remains modest. Therefore, early identification of patients likely to recur and treatment after recurrence remain critical unmet needs in the clinical care of bladder cancer patients. To address these deficits, a better understanding of the mechanisms of resistance to BCG-therapy is needed. The virtual update of the International Bladder Cancer Network (IBCN) on the biology of response to BCG focused on potential mechanisms and markers of resistance to intravesical BCG therapy. The insights from this meeting will be highlighted and put into context of previously reported mechanisms of resistance to BCG in this review.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Bacillus Calmette-Guerin (BCG); Bladder cancer; Immunotherapy